2019
DOI: 10.1155/2019/2056085
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Promotes the Interaction between the Tumor, Macrophages, and T Cells to Regulate the Progression of Chemically Induced Colitis-Associated Colorectal Cancer

Abstract: Colitis-associated colorectal cancer (CRC) development has been shown to be related to chronically enhanced inflammation. Macrophage migration inhibitory factor (MIF) is an inflammatory mediator that favors inflammatory cytokine production and has chemotactic properties for the recruitment of macrophages (Møs) and T cells. Here, we investigated the role of MIF in the inflammatory response and recruitment of immune cells in a murine model of chemical carcinogenesis to establish the impact of MIF on CRC genesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…It was reported that hemogram parameters can be used to predict the prognosis of cancer and provide a basis for judging the prognosis of cancer ( 15 , 16 ), and inflammation is related to the occurrence and development of cancer ( 17 , 18 ). A series of inflammatory indexes have been reported to participate in tumor progress, such as MLR, NLR and PLR.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that hemogram parameters can be used to predict the prognosis of cancer and provide a basis for judging the prognosis of cancer ( 15 , 16 ), and inflammation is related to the occurrence and development of cancer ( 17 , 18 ). A series of inflammatory indexes have been reported to participate in tumor progress, such as MLR, NLR and PLR.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological role of MIF in a wide range of inflammatory diseases, among which IBD, was already demonstrated (Nishihira and Mitsuyama, 2009). Increased MIF in macrophages in a CRC mouse model was demonstrated, and loss of MIF expression protects mice during tumor initiation (Pacheco-Fernández et al, 2019;Klemke et al, 2021). In cancer cells from CRC patients and in an acute colitis-CRC mouse model, a tumor-specific elevation of MIF expression was demonstrated (Klemke et al, 2021).…”
Section: Inflammation and Tumorigenesis In Ibd-crcmentioning
confidence: 98%
“… 60 Macrophage migration inhibitory factor [MIF] mediates macrophage and T-cell recruitment and MIF −/− mice treated with AOM/DSS have an increased tumour burden, associated with lower levels of macrophages. 61 Fibrinogen-like protein 2 [Fgl2] may be important for macrophage recruitment with/without polarization as Fgl2 loss induces M1-polarized and suppresses M2-polarized macrophages; Fgl2 may therefore reduce inflammation and IBD-CRC. 62 In contrast, TGFβ promotes macrophage recruitment through expression of CCR2 in the tumour microenvironment, and myeloid-cell TGFβ2 expression worsens AOM/DSS-induced tumorigenesis.…”
Section: Dysregulation Of Critical Immune-mediated Pathways In Ibd-crcmentioning
confidence: 99%